Building dynamic capabilities for high margin product development: a corporate control style perspective. Issue 1 (2nd January 2020) - Garri, Myropi; Spicer, Lee A.; Pereira, Vijay; Temouri, Yama; Malik, Ashish; Tarba, Shlomo
Abstract: This article contributes to the dynamic capabilities (DCs) literature by exploring the link between sensing, seizing and reconfiguring and firm performance defined as commercially successful high margin products development (HMPD). Our qualitative findings are based on semi-structured interviews conducted within a multinational telecommunication corporation. Our qualitative findings show that the sensing, seizing and reconfiguring aspects of DCs positively influence firm performance. Moreover, the level of positive influence of DCs on performance depends on the corporate control style (CCS) of the firm, since CCS directly affects the seizing and reconfiguring activities of DCs. CCS also regulates the link between sensing and seizing DCs activities and firm performance. We find evidence that there is no specific order in which the sensing, seizing, and reconfiguring activities occur. We also find that the identification of 'Surge' and 'Lurch'events is a key channel for managers to enhance DCs in their firms.